2018
DOI: 10.1002/erv.2593
|View full text |Cite
|
Sign up to set email alerts
|

Different attention bias patterns in anorexia nervosa restricting and binge/purge types

Abstract: Patients with anorexia nervosa (AN) have been shown to display both elevated anxiety and attentional biases in threat processing. In this study, we compared threat-related attention patterns of patients with AN restricting type (AN-R; n = 32), AN binge/purge type (AN-B/P; n = 23), and healthy controls (n = 19). A dot-probe task with either eating disorder-related or general and social anxiety-related words was used to measure attention patterns. Severity of eating disorder symptoms, depression, anxiety, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Moreover, patients with recANr showed greater activation of the visual cortex than did those with recANbp. This is consistent with a previous study reporting that patients with restricting AN had a larger attentional bias to threat word stimuli related to ED (e.g., FAT) than did healthy controls, whereas patients with binge-purging AN showed avoidance of threat word stimuli related to ED [ 56 ]. Our result suggests that differential patterns of attention allocation between patients with restricting AN and those with binge purging AN may remain even after recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, patients with recANr showed greater activation of the visual cortex than did those with recANbp. This is consistent with a previous study reporting that patients with restricting AN had a larger attentional bias to threat word stimuli related to ED (e.g., FAT) than did healthy controls, whereas patients with binge-purging AN showed avoidance of threat word stimuli related to ED [ 56 ]. Our result suggests that differential patterns of attention allocation between patients with restricting AN and those with binge purging AN may remain even after recovery.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no mention as to subtyping the patients in this study to restrictive vs. binge/purge pathology. It is of note, in this respect, that a previous study of our group [69], found a significant difference in attention bias patterns between patients with AN-R and AN-B/P, an issue not investigated in previous studies assessing attention bias in AN.…”
Section: Discussionmentioning
confidence: 52%
“…The general and social threat words were taken from Bar-Haim et al (2010) assessing the use of ABMT in different types of anxiety. The ED-related threat words were used in our previous study of attention bias in AN (Gilon-Mann et al, 2018). They were first rated for emotional valence by 15 independent judges working in the adult and adolescent ED departments of the Sheba Medical Center (clinical psychologists, clinical social workers, psychiatrists and dieticians -all not part of the research team).…”
Section: Instrumentsmentioning
confidence: 99%